A STUDY ON APPROPRIATE USAGE OF FRESH FROZEN PLASMA AND ALBUMIN FOR PATIENTS IN INTERNAL MEDICINE - Ishii, Kayo; Takada, Yuko; Takagi, Tomoko; Fujita, Hiroshi; Takeda, Toshio; Teratani, Miyuki; Kodo, Hideki; Yazawa, Yurika; Kajiro, Kazumasa; Tanikawa, Shu; Yamamoto, Emi; Hiruma, Kiyoshi (Journal of the Japan Society of Blood Transfusion, 2004)
We evaluated the appropriateness of usage of fresh frozen plasma (FFP) and albumin for patients in internal medicine in seven general of Tokyo Metropolitan hospitals according to blood usage guidelines revised in 1999. We investigated patients with hepatoma or disseminated intravascular coagulation (DIC) in 1999, and all patients in internal medicine except for those undergoing plasma exchange in 2000. The total number of patients entered in the study for FFP and albumin was 279 and 250, respectively. FFP transfusion was judged appropriate when used in patients whose prothrombin time (PT) was 30% or less. Albumin administration was judged appropriate if used for patients with hypoalbuminemia below 3.0g/dL and with circulation failure, or in patients with hypoalbuminemia below 2.5g/dL without circulation failure. We judged the usage of FFP or albumin to be inappropriate if the PT value of patients for FFP or serum albumin value of patients for albumin was not measured before usage. Appropriate usage rate of FFP in patients with hepatoma or DIC was 16.2% in 1999 and 20.8% in 2000. In contrast, the appropriate usage rate of albumin from 1999 to 2000 was 65.2%. This study will help in assessing the degree of publicity received by the blood usage guidelines and the future direction of this publicity.